Adaptation of Problem-Solving Treatment for Prevention of Depression Among Low-Income, Culturally Diverse Mothers - Feinberg, Emily (Fam Community Health, 2012)
Adapting evidence-based interventions to be more accessible and culturally sensitive to the needs of diverse populations is a potential strategy to address disparities in mental health care. We adapted an evidence-based depression-treatment strategy, Problem-Solving Treatment, to prevent depression among low-income mothers with vulnerable children. Intervention adaptations spanned 3 domains: (1) the intervention’s new prevention focus, (2) conducting a parent-focused intervention in venues oriented to children; and (3) cultural competency. The feasibility of adaptations was assessed through 2 pilot-randomized trials (n = 93), which demonstrated high participant adherence, satisfaction, and retention, demonstrating the feasibility of our adaptations.